„Język śląski” – czyli o mieszaniu porządków - Siuciak, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
This article provides an overview of the complex situation surrounding ongoing efforts to legalise Silesian as a regional language. The debate on this issue is multifaceted, involving an interplay of scientific, political and social dimensions. This mixing of orders leads to a deconstruction of traditional concepts such as language and dialect. Two primary positions emerge in the academic discussion. The traditional view, grounded in linguistic arguments, classifies Silesian as a dialect of the Polish language. In contrast, the opposing view, based on socio-political considerations, asserts that the former Silesian dialect has evolved into a language distinct from Polish. The most accurate perspective for describing the current situation seems to be an intermediate one. According to this view, Silesian, due to its rich body of literature and presence in the public sphere, has transcended the boundaries of a dialect. It now meets the criteria of a regiolect, which will continue to undergo codification and normative development – though this will be a long-term process.